Distinct fermentation of human milk oligosaccharides 3-FL and LNT2 and GOS/inulin by infant gut microbiota and impact on adhesion of Lactobacillus plantarum WCFS1 to gut epithelial cells. Issue 24 (23rd November 2021) - Kong, Chunli; Akkerman, Renate; Klostermann, Cynthia E.; Beukema, Martin; Oerlemans, Marjolein M. P.; Schols, Henk A.; de Vos, Paul
Abstract : Fermentation of hMOs 3-FL and LNT2 by infant gut microbiota is structure dependent and different from the commonly applied GOS/inulin, and the fermentation digesta may lead to differential potencies to stimulate the commensal bacteria colonizaiton. Abstract : Human milk oligosaccharides (hMOs) are unique bioactive components in human milk. 3-Fucosyllactose (3-FL) is an abundantly present hMO that can be produced in sufficient amounts to allow application in infant formula. Lacto- N -triaose II (LNT2) can be obtained by acid hydrolysis of lacto- N -neotetraose (LNnT). Both 3-FL and LNT2 have been shown to have health benefits, but their impact on infant microbiota composition and microbial metabolic products such as short-chain fatty acids (SCFAs) is unknown. To gain more insight in fermentability, we performed in vitro fermentation studies of 3-FL and LNT2 using pooled fecal microbiota from 12-week-old infants. The commonly investigated galacto-oligosaccharides (GOS)/inulin (9 : 1) served as control. Compared to GOS/inulin, we observed a delayed utilization of 3-FL, which was utilized at 60.3% after 36 h of fermentation, and induced the gradual production of acetic acid and lactic acid. 3-FL specifically enriched bacteria of Bacteroides and Enterococcus genus. LNT2 was fermented much faster. After 14 h of fermentation, 90.1% was already utilized, and production of acetic acid, succinic acid, lactic acid and butyric acid was observed. LNT2 specifically increased the abundance of Collinsella, as well as Bifidobacterium. The GOS present in the GOS/inulin mixture was completely fermented after 14 h, while for inulin, only low DP was rapidly utilized after 14 h. To determine whether the fermentation might lead to enhanced colonization of commensal bacteria to gut epithelial cells, we investigated adhesion of the commensal Lactobacillus plantarum WCFS1 to Caco-2 cells. The fermentation digesta of LNT2 collected after 14 h, 24 h, and 36 h, and GOS/inulin after 24 h of fermentation significantly increased the adhesion of L. plantarum WCFS1 to Caco-2 cells, while 3-FL had no such effect. Our findings illustrate that fermentation of hMOs is very structure-dependent and different from the commonly applied GOS/inulin, which might lead to differential potencies to stimulate adhesion of commensal cells to gut epithelium and consequent microbial colonization. This knowledge might contribute to the design of tailored infant formulas containing specific hMO molecules to meet the need of infants during the transition from breastfeeding to formula.